Measuring the Level of Strategic Intelligence Among University Students A Field Study on Fourth-Year Students in the Faculty of Economics, Tishreen University - متوج على; سامر قاسم; جميل عيسى (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to determine the level of strategic intelligence in its dimensions (foreseeing, systems thinking, future vision, motivation, partnership) among a sample of fourth-year students from the Faculty of Economics at Tishreen University. The research relied on the analytical descriptive approach, and the research community included all fourth-year students at the Faculty of Economics at Tishreen University, whose number is (1100) male and female students. male and female students, the questionnaire was distributed to them, and (273) completed questionnaires were returned, valid for statistical analysis, with a response rate of (95.79%). The results showed that the level of strategic intelligence among the sample of fourth-year students at the Faculty of Economics at Tishreen University was significant, and with relative importance (74.88%). As for the dimensions, they were arranged according to the following: foresight, future vision, partnership, motivation, and systems thinking.